70.2k views
1 vote
Someone help me pliz

Someone help me pliz-example-1
User Jmohr
by
5.2k points

1 Answer

4 votes

Answer:

B(2, - 1 )

Explanation:

Given endpoints (x₁, y₁ ) and (x₂, y₂ ) then the midpoint is

(
(x_(1)+x_(2) )/(2),
(y_(1)+y_(2) )/(2) )

let the coordinates of B = (x, y )

Then using the midpoint formula, equate to each coordinate of the given midpoint, that is

(x₁, y₁ ) = A(4, 3) and (x₂, y₂ ) = B(x, y) , then


(4+x)/(2) = 3 ( multiply both sides by 2 )

4 + x = 6 ( subtract 4 from both sides )\

x = 2


(3+y)/(2) = 1 ( multiply both sides by 2 )

3 + x = 2 ( subtract 3 from both sides )

x = - 1

Coordinates of B = (2, - 1 )

User Ventrilocus
by
5.9k points